Perancangan Jaringan VPN Menggunakan Metode Point To Point Tunneling Protocol - Bambang Supriyanto; Suharyanto Suharyanto (Universitas Bina Sarana Informatika, 2019)
PT. Hail Otis Logistics is a Forwarding and Expedition Company that provides Custom Clearence Export and Import services as well as Shipping or Delivery from Partner Companies to Tanjung Priuk Port and vice versa. Currently PT. Hail Otis Logistics is sending company data using e-mail, so the company cannot yet ensure the security of the data sent. Due to the company's problems, designing a VPN is a means of communicating and transferring data securely and maintaining data validity. In this study VPN was built using the PPTP (Point To Point Tunneling Protocol) method to build a VPN network at PT. Hail Otis Logistics. Use PPTP because this method uses a protocol that allows point to point relationships that pass through the IP network. Results obtained in VPN development at PT. Hail Otis Logistics are VPN networks that can connect between headquarters and branch offices to transfer data safely. VPN development can provide security with encryption in every data communication.Keywords: PPTP, Network, VPN